Sweetest Protein -Thaumatin - Dahal, Nawa Raj; Xu, XM (Journal of Food Science and Technology Nepal, 2014)
Thaumatin, commercially available under the trade name Talin, is known as a sweetest compound (100,000 times sweeter than sucrose on molar basis) which can be used not only as a sweetener but also as a flavor enhancer. This sweetener is a protein found in plant Thaumatococcus daniellii. Biotechnology has also seen as alternative method of production of thaumatin. The plant source of this protein is limited and very expensive. Although the sweetener is the sweetest one, its application is not so common because of its liquorice taste and delayed sweetness. This article reviews brie y on the property, production, application and safety aspects of Thaumatin which is known as a sweetest compound till date. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.11210 J. Food Sci. Technol. Nepal, Vol. 7 (112-118), 2012